3(5-x)-4(3x-2)=3

Simple and best practice solution for 3(5-x)-4(3x-2)=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(5-x)-4(3x-2)=3 equation:


Simplifying
3(5 + -1x) + -4(3x + -2) = 3
(5 * 3 + -1x * 3) + -4(3x + -2) = 3
(15 + -3x) + -4(3x + -2) = 3

Reorder the terms:
15 + -3x + -4(-2 + 3x) = 3
15 + -3x + (-2 * -4 + 3x * -4) = 3
15 + -3x + (8 + -12x) = 3

Reorder the terms:
15 + 8 + -3x + -12x = 3

Combine like terms: 15 + 8 = 23
23 + -3x + -12x = 3

Combine like terms: -3x + -12x = -15x
23 + -15x = 3

Solving
23 + -15x = 3

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-23' to each side of the equation.
23 + -23 + -15x = 3 + -23

Combine like terms: 23 + -23 = 0
0 + -15x = 3 + -23
-15x = 3 + -23

Combine like terms: 3 + -23 = -20
-15x = -20

Divide each side by '-15'.
x = 1.333333333

Simplifying
x = 1.333333333

See similar equations:

| 86-2x=25x+23 | | 139-5x=22x+22 | | 5x^2+8x=-19 | | 5x^2+8x=19 | | X+7=4(3x-2) | | 9-9x=45-16x | | 134x-(120000+82x)=560000 | | 5(8-3n)+5n=40+20n | | 9y=2x | | G=4(x+9)-(7+x)(x+1) | | (4b^3+9b^2-6)+(3b^3-9b+8)= | | Y+9=-2 | | 8(6x-1)=6x+1 | | -(6y+1)-(5y-8)=1 | | -79-10x=7*23 | | u-3u=10+8 | | y=-11+6x | | 8+5m-1=9m+11-3 | | 8v=-7 | | 3(x+2)+2(3x+2)=28 | | 2(4-2x+x^2)-x(x+2)= | | 33x-10-17x=4(4x-3)+2 | | 1+3n-5n=12 | | 6r-4r=16 | | 8x+14x=132 | | 16x^2+38x-5=0 | | (3x+5)-(-7x+8)= | | 2y-3x=0 | | 5(3+6x)-5=70 | | -7g=49 | | 4(4x+2)=20-2(x-3) | | x^4-81-x^3+9=0 |

Equations solver categories